Impact of rest breaks on musculoskeletal discomfort of Chikan embroiderers of West Bengal, India: a follow up field study. Issue 4 (22nd July 2016) - Chakrabarty, Sabarni; Sarkar, Krishnendu; Dev, Samrat; Das, Tamal; Mitra, Kalpita; Sahu, Subhashis; Gangopadhyay, Somnath
Abstract : Objectives: This study aimed to determine risk factors that predict musculoskeletal discomfort in Chikan embroiderers of West Bengal, India, and to compare the effect of two rest break schedules to reduce these symptoms. Methods: The Nordic musculoskeletal questionnaire was performed on 400 Chikan embroiderers at baseline containing questions on job autonomy, working behavior, and work stress factors. Relative risk was calculated to identify prognostic factors for musculoskeletal discomfort in different body regions. Two groups of workers received two rest break schedules for 4 months and compared in a between‐subject design. Outcome variables were scores of Body Part Discomfort (BPD) scale. Results: Chikan embroiderers are afflicted with musculoskeletal discomfort mainly in the lower back, neck/shoulder and wrist/forearm region, which is attributed to their prolonged working timeinvolving hands and wrists, being in a static seating posture. Rigidity in working methods, prolonged working time, inadequate rest break during the working day, dissatisfaction regarding earning, monotonous work, static sitting posture, and repetitive movement of wrist and forearm were the significant predictors of these symptom developments. Rest break schedule 1 with more frequent and shorter breaks had more significant improvement on the severity of these musculoskeletal discomforts. Conclusions: Chikan embroiderers perform a highly dreary occupation and various ergonomics conditions work as predictors for developing musculoskeletal discomforts among them. Design of proper rest break schedule involving shorter and frequent breaks was competent for reducing these discomforts to a certain extent.